Attention-Deficit Hyperactivity in Elementary School Children in Ulaanbaatar: Incidence, Subtypes and Influencing Factors - Bayarsaikhan, Amgalan; Ganbaatar, Erdenetuya; Avirmed, Tovuudorj; Ganbat, Otgontuul; Ariyasuren, Khulan; Enkhtuya, Khulan (Central Asian Journal of Medical Sciences, 2019)
Objectives: This study aimed to determine the incidence of Attention-Deficit/Hyperactivity Disorder (ADHD) among primary school children in Ulaanbaatar and identify some of the influencing factors and specific clinical features. Methods: A total of 973 primary school children between 6 – 13 years of age in grades 2-5, along with 973 parents/caretakers, and 91 class teachers were recruited from secondary schools of Ulaanbaatar, Mongolia. Results: ADHD prevalence for the 973 participants was 16.6% based on teacher’s reports and 9.7% based on parent’s reports. Using the criteria that both the teacher and parent/caretaker both reported ADHD for a child, 50 children were diagnosed with ADHD, and the estimated prevalence was 5.8% in Ulaanbaatar. Among the 50 children with ADHD, 78% were boys, 22% were girls, with ADHD being four times more common in boys than girls (p =.0001). The constituent ratios of ADHD-Inattentive, ADHD-Hyperactive/impulsive, and ADHD-Combined subtypes were 4.07%, 3.3%, and 1.5%, respectively. The risks were 7.5 times higher when the mother smoked during pregnancy and 2.9 times higher when the child lived with a grandparent than with both parents (p<.05). Conclusion: Our findings suggest that the incidence of ADHD among children in Ulaanbaatar is consistent with previous studies conducted in other countries and regions.